MUSEUM BAWAH AIR M. V. BOELONGAN: SEBUAH GAGASAN PEMBAHARUAN MUSEUM - Dwi Kurnia Sandy; Kusumastuti Salma Fitri (WalennaE, 2019)
Museum is not only a place for storing various artifacts, but also as a media of learning. However, the current management of museums in Indonesia is still not serving visitors well. Museum is not only located on the land, but there are also underwater museums. The plan of build an underwater museum has been discussed by museum practitioners and academics. Many locations and objects that could be used as underwater museums in Indonesia, one of that is the M.V Boelongan Shipwreck. This ship was sunk by Japanese Army during the Second World War. Nowadays, M.V. Boelongan has been an attractive destination for tourism activities, such as diving. To make it more benefit, not only in economic, but also in education and preservation, build and design this shipwreck as museum is one of the best solution. It could give the chance to everyone to see the shipwreck without diving. This museum should be plan to have a modern design, easier to educate and entertain the visitors, and also to preserve it as a heritage. M.V Boelongan is a part of Indonesian maritime history, the important values should be preserved and published to the public. Selain menjadi tempat penyimpanan berbagai artefak, museum juga menjadi media pembelajaran. Namun, saat ini pengelolaan museum di Indonesia masih kurang melayani pengunjung. Museum terdapat di darat dan di perairan. Isu pembuatan museum bawah air sudah menjadi pembahasan di kalangan pecinta museum. Banyak lokasi dan objek dapat dijadikan museum bawah air di Indonesia, salah satunya adalah Kapal M.V. Boelongan. Keberadaan M.V. Boelongan menjadi sebuah daya tarik pariwisata, diantaranya wisata selam. Pembuatan museum bawah air adalah salah satu alternatif yang dapat memberikan manfaat di bidang ekonomi, pendidikan dan pelestarian. Museum Bawah Air M.V. Boelongan memungkinkan pengunjung yang tidak dapat menyelam tetap dapat menyaksikan keberadaan M.V. Boelongan di bawah air. Museum akan dirancang sesuai dengan perkembangan zaman, baik dari sisi pengelolaan maupun perancangan. Hal ini sejalan dengan paradigma museum yang sejak lama digadang-gadang, yaitu membuat museum yang mengedukasi sekaligus memberikan hiburan bagi pengunjungnya. Selain itu, dengan adanya museum dapat melindungi keberadaan bangkai kapal dan menjadi salah satu cara untuk menjaga kelestarian M.V. Boelongan. M.V Boelongan adalah bagian dari sejarah kemaritiman di Indonesia. Tinggalan budaya materi ini patut dilestarikan dan disampaikan nilai-nilainya